Negative electrode material true density testing method and application thereof

By pressing the negative electrode material into molding, infiltrating it with an electrolyte solvent, and calculating the true density using the nuclear magnetic signal, the problem of inaccurate testing of the negative electrode material in the prior art is solved, and higher measurement accuracy and more suitable battery cell design are achieved.

CN119779909AInactive Publication Date: 2025-04-08BEIJING HINA BATTERY TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411948389.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When testing the true density of the negative electrode material, the use of the BET method results in the excessive true density, making it impossible to accurately design the amount of electrolyte injection, affecting the electrochemical performance of the battery.

Method used

The method of pressing the negative electrode material into molding and infiltrating it with an electrolyte solvent is used, and the mass of the electrolyte solvent in the negative electrode sample is calculated by using a hydrogen atom as a probe, thereby calculating the true density of the negative electrode material.

Benefits of technology

It improves the measurement accuracy of the true density of the negative electrode material, simplifies operation, and is suitable for battery cell injection volume design, with the advantages of fast test speed, high sensitivity and losslessness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119779909A_ABST
    Figure CN119779909A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative electrode material true density testing method and application thereof. The negative electrode material true density testing method comprises the following steps: mixing a to-be-tested negative electrode material with a binder or mixing the to-be-tested negative electrode material, a conductive agent and the binder, and then pressing and drying to obtain a dried sample; infiltrating the dry sample in an electrolyte solvent, taking out the dry sample, and removing the electrolyte solvent on the surface of the infiltrated sample to obtain a negative electrode sample; and respectively carrying out nuclear magnetic resonance testing on the dried sample and the negative electrode sample, and then calculating to obtain the true density of the negative electrode material. According to the method, the true density of the negative electrode material can be calculated, the obtained true density is high in accuracy, and the method is more suitable for cell liquid injection quantity design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a method for testing the true density of a negative electrode material and an application thereof. Background Art

[0002] In recent years, ion batteries have been widely used in many fields of daily life. In order to meet the growing electrochemical energy storage needs of human society, the comprehensive performance of existing ion batteries needs to be improved. Among them, the negative electrode material of the battery plays an important role in the development of the battery. Currently common carbon-based negative electrode materials include graphite carbon materials, amorphous carbon materials and nano-carbon materials. The true density of the negative electrode material is one of the important parameters in the battery design process. It is related to the design of the electrolyte injection volume ratio and affects the electrochemical performance of the battery.

[0003] Existing technologies often use the BET method to test the true density of negative electrode materials. However, the size of helium atoms is much smaller than that of electrolyte molecules and can enter tiny pores that electrolyte molecules cannot enter. Therefore, the true density tested by the BET method is too large, which leads to inaccurate design of the liquid injection amount when used in battery cell design.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first purpose of the present invention is to provide a method for testing the true density of negative electrode materials. After the negative electrode material is pressed into shape, it is infiltrated with an electrolyte solvent and hydrogen atoms are used as probes. Since the content of hydrogen atoms in the sample is proportional to the intensity of the nuclear magnetic resonance signal, the mass of the electrolyte solvent in the negative electrode sample can be calculated through the nuclear magnetic resonance signal, and then the true density of the negative electrode material can be calculated. The obtained true density has high accuracy and is easy to operate, and is more suitable for the design of battery cell injection volume.

[0006] The second object of the present invention is to provide an application of a method for testing the true density of negative electrode materials in the preparation of secondary batteries.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] The present invention first provides a method for testing the true density of negative electrode materials, comprising the following steps: mixing the negative electrode material to be tested with a binder or mixing the negative electrode material to be tested, a conductive agent and a binder, and then pressing and drying to obtain a dry sample; soaking the dry sample in an electrolyte solvent, removing the electrolyte solvent on the surface of the soaked sample after taking it out, and obtaining a negative electrode sample; performing nuclear magnetic resonance tests on the dry sample and the negative electrode sample respectively, and then obtaining the true density of the negative electrode material by calculation.

[0009] Furthermore, before the calculation, the nuclear magnetic resonance signal amount of the electrolyte solvent at different masses is measured, and the linear equation is obtained by taking the nuclear magnetic resonance signal amount as the dependent variable and the mass of the electrolyte solvent as the independent variable.

[0010] Furthermore, the nuclear magnetic resonance signal of the dry sample is measured to be A0, and the nuclear magnetic resonance signal of the negative electrode sample is measured to be A1, A=A1-A0, wherein A is the nuclear magnetic resonance signal corresponding to the pore volume of the negative electrode sample.

[0011] Furthermore, the calculation method includes: substituting A into the linear equation to obtain the mass m0 of the electrolyte solvent in the negative electrode sample, and then calculating the true density ρ of the negative electrode material. H .

[0012] Furthermore, the true density of the negative electrode material is H The specific calculation methods include:

[0013] V0=m 0 / ρ0; wherein, m0 is the mass of the electrolyte solvent in the negative electrode sample, in g; ρ0 is the density of the electrolyte solvent, in g / cm 3 .

[0014] in, is the porosity of the negative electrode sample; V0 is the volume of the electrolyte solvent, in cm 3 ; V1 is the volume of the negative electrode sample, in cm 3 .

[0015] V2 = V1 - V0; wherein V2 is the total solid volume of the negative electrode sample, in cm 3 .

[0016] V3=m1×P1 / ρ P ; Wherein, V3 is the volume of the binder, in cm 3 ; m1 is the mass of the negative electrode sample, in g; P1 is the mass fraction of the binder in the dry sample; ρ P is the true density of the binder, in g / cm 3 .

[0017] V4=m1×P2 / ρ S ; Wherein, V4 is the volume of the conductive agent, in cm 3 ; P2 is the mass fraction of the conductive agent in the dry sample; ρ S is the true density of the conductive agent, in g / cm 3 .

[0018] V5 = V2 - V3 - V4; wherein V5 is the true volume of the negative electrode material, in cm 3 .

[0019] ρ H =m1×P H / V5; where P H is the mass fraction of the negative electrode material in the dry sample; ρ H The unit is g / cm 3 .

[0020] Furthermore, the shape of the negative electrode sample is a cylinder, and V1=π×(d / 2) 2 ×h; wherein, d is the diameter of the negative electrode sample, in cm; h is the height of the negative electrode sample, in cm.

[0021] Furthermore, the shape of the negative electrode sample is a rectangular parallelepiped, and V1=a×b×h; wherein a is the length of the negative electrode sample, in cm; b is the width of the negative electrode sample, in cm; and h is the height of the negative electrode sample, in cm.

[0022] Furthermore, the shape of the negative electrode sample is a sphere, and V1=(4 / 3)×π×r 3 ; Wherein, r is the radius of the negative electrode sample, in cm.

[0023] Furthermore, the shape of the negative electrode sample is a prism, and V1=S×h; wherein S is the bottom area of ​​the negative electrode sample, in cm 2 ; h is the height of the negative electrode sample, in cm.

[0024] Furthermore, the negative electrode material includes at least one of a carbon material, a silicon material and a silicon-carbon composite material.

[0025] Further, the conductive agent includes at least one of conductive carbon black SP, graphite, superconducting carbon, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0026] Furthermore, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, styrene-butadiene rubber, water-based acrylic resin and carboxymethyl cellulose.

[0027] Furthermore, the mass ratio of the negative electrode material, the conductive agent and the binder is 50-99:0-25:0.1-25.

[0028] Furthermore, the electrolyte solvent includes at least one of an ether solvent and an ester solvent.

[0029] Furthermore, the nuclear magnetic resonance test includes a low-field nuclear magnetic resonance test.

[0030] Furthermore, the magnetic field strength of the nuclear magnetic resonance test is ≤1.0T.

[0031] Furthermore, the echo time of the nuclear magnetic resonance test does not exceed 5 ms.

[0032] Furthermore, the number of echoes of the nuclear magnetic resonance test is not less than 10,000.

[0033] Furthermore, the waiting time of the nuclear magnetic resonance test does not exceed 10000 ms.

[0034] Furthermore, the cumulative sampling times of the nuclear magnetic resonance test is no less than 4 times.

[0035] Furthermore, the infiltration is performed under vacuum conditions, and the vacuum degree of the infiltration is 0.1-0.5 MPa.

[0036] Furthermore, the infiltration time is ≥2h.

[0037] The present invention further provides application of the negative electrode material true density testing method in preparing secondary batteries.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The present invention provides a method for testing the true density of negative electrode materials. After the negative electrode material is pressed into shape, it is soaked with an electrolyte solvent and hydrogen atoms are used as probes. Since the content of hydrogen atoms in the sample is proportional to the intensity of the nuclear magnetic resonance signal, the mass of the electrolyte solvent in the negative electrode sample can be calculated through the nuclear magnetic resonance signal, and then the true density of the negative electrode material can be calculated. The obtained true density has high accuracy and is easy to operate.

[0040] (2) The method for testing the true density of negative electrode materials provided by the present invention tests the porosity of negative electrode materials when they are immersed in electrolyte solvents, excluding tiny pores that cannot be entered by electrolyte solvent molecules. The obtained true density is more suitable for the design of battery cell filling volume, and has the advantages of fast testing speed, high sensitivity and non-destructiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1The marking line equation obtained by fitting the embodiment 1 provided by the present invention;

[0043] Figure 2 This is the marking line equation obtained by fitting in Example 2 provided by the present invention. DETAILED DESCRIPTION

[0044] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0045] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0046] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0047] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0048] In a first aspect, the present invention provides a method for testing the true density of a negative electrode material, which is a method for rapidly and non-destructively testing the true density of a negative electrode material, comprising the following steps:

[0049] The negative electrode material to be tested is mixed evenly with the binder, or the negative electrode material to be tested, the conductive agent and the binder are mixed evenly, and then pressed into a sample using a tablet pressing mold, and dried to obtain a dry sample.

[0050] The dried sample is immersed in an electrolyte solvent, taken out after the immersion is completed, and the electrolyte solvent on the surface of the immersed sample is removed to obtain a negative electrode sample.

[0051] The dry sample and the negative electrode sample are respectively subjected to nuclear magnetic resonance testing, and then the porosity of the tested samples is obtained by inversion calculation, and then the true density of the negative electrode material to be tested is obtained by calculation.

[0052] The present invention provides a method for testing the true density of negative electrode materials. After the negative electrode material is pressed into shape, it is infiltrated with an electrolyte solvent and hydrogen atoms are used as probes. Since the content of hydrogen atoms in the sample is proportional to the intensity of the nuclear magnetic resonance signal, the mass of the electrolyte solvent in the negative electrode sample can be calculated through the nuclear magnetic resonance signal, and then the true density of the negative electrode material can be calculated.

[0053] The present invention performs true density testing in an environment simulating electrolyte infiltration, which can exclude tiny pores in the material. The obtained true density data has high accuracy and is easy to operate, and is more suitable for designing the liquid injection amount of a battery cell.

[0054] In some specific embodiments, before the calculation, the nuclear magnetic resonance signal amount of the electrolyte solvent at different masses is measured (i.e., the nuclear magnetic resonance signal amount of electrolyte solvents of different masses is measured), and the nuclear magnetic resonance signal amount is used as the dependent variable and the mass of the electrolyte solvent is used as the independent variable to obtain a linear equation, i.e., the relationship between the mass of the electrolyte solvent and the nuclear magnetic resonance signal amount.

[0055] The relationship can be y=kx+b, where x is the mass of the electrolyte solvent, y is the nuclear magnetic resonance signal, k is the slope, and b is the intercept. After determining the linear equation or relationship, the mass of the electrolyte solvent can be calculated by substituting the nuclear magnetic resonance signal, slope, and intercept.

[0056] In some specific embodiments, the nuclear magnetic resonance signal of the dry sample is measured to be A0, and the nuclear magnetic resonance signal of the negative electrode sample is measured to be A1, A=A1-A0, wherein A is the nuclear magnetic resonance signal corresponding to the pore volume of the negative electrode sample (the pore volume corresponds to the T2 spectrum signal).

[0057] In some specific embodiments, the calculation method includes: substituting A into the linear equation to obtain the mass m0 of the electrolyte solvent in the negative electrode sample, and then calculating the true density ρ of the negative electrode material H .

[0058] In some specific embodiments, the true density of the negative electrode material is H The specific calculation methods include:

[0059] V0=m 0 / ρ0; wherein, m0 is the mass of the electrolyte solvent in the negative electrode sample, in g; ρ0 is the density of the electrolyte solvent, in g / cm 3The volume of the electrolyte solvent can be calculated from the mass of the electrolyte solvent and the density of the electrolyte.

[0060] in, is the porosity of the negative electrode sample (%); V0 is the volume of the electrolyte solvent, in cm 3 ; V1 is the volume of the negative electrode sample, in cm 3 .

[0061] Using the porosity of the negative electrode sample The total solid volume of the negative electrode sample can be calculated, and the volume of the binder and the volume of the conductive agent can be subtracted to obtain the true volume of the negative electrode active material in the sample.

[0062] V2 = V1 - V0; wherein V2 is the total solid volume of the negative electrode sample, in cm 3 .

[0063] V3=m1×P1 / ρ P ; Wherein, V3 is the volume of the binder, in cm 3 ; m1 is the mass of the negative electrode sample, in g; P1 is the mass fraction of the binder in the dry sample; ρ P is the true density of the binder, in g / cm 3 .

[0064] V4=m1×P2 / ρ S ; Wherein, V4 is the volume of the conductive agent, in cm 3 ; P2 is the mass fraction of the conductive agent in the dry sample; ρ S is the true density of the conductive agent, in g / cm 3 .

[0065] V5 = V2 - V3 - V4; wherein V5 is the true volume of the negative electrode material, in cm 3 .

[0066] The true density of the negative electrode material can be calculated using the mass of the negative electrode sample and the true volume of the negative electrode material in the negative electrode sample.

[0067] ρ H =m1×P H / V5; where P H is the mass fraction of the negative electrode material in the dry sample; ρ H The unit is g / cm 3 .

[0068] The present invention tests the porosity of the negative electrode material when it is soaked in electrolyte solvent, excludes tiny pores that the electrolyte solvent molecules cannot enter, and the obtained true density is more suitable for the design of battery cell injection volume, and has the advantages of fast testing speed, high sensitivity and non-destructiveness.

[0069] In some specific embodiments, the shape of the negative electrode sample is a cylinder, and V1=π×(d / 2) 2 ×h; wherein, d is the diameter of the negative electrode sample, in cm; h is the height of the negative electrode sample, in cm.

[0070] In some specific embodiments, the shape of the negative electrode sample is a rectangular parallelepiped, and V1=a×b×h; wherein a is the length of the negative electrode sample, in cm; b is the width of the negative electrode sample, in cm; and h is the height of the negative electrode sample, in cm.

[0071] In some specific embodiments, the shape of the negative electrode sample is a sphere, and V1 = (4 / 3) × π × r 3 ; Wherein, r is the radius of the negative electrode sample, in cm.

[0072] In some specific embodiments, the shape of the negative electrode sample is a prism, and V1=S×h; wherein S is the bottom area of ​​the negative electrode sample, in cm 2 ; h is the height of the negative electrode sample, in cm.

[0073] In some specific embodiments, the negative electrode material includes at least one of a carbon material, a silicon material and a silicon-carbon composite material.

[0074] The carbon material includes any material commonly used in the art or disclosed in the prior art, such as graphite carbon material, amorphous carbon material, nano carbon material, etc., but is not limited thereto.

[0075] The silicon material includes, but is not limited to, elemental silicon and / or silicon oxide.

[0076] The silicon-carbon composite material includes any composite material containing carbon and silicon commonly used in the art.

[0077] In some specific embodiments, the conductive agent includes any conductive material commonly used in the art, such as at least one of conductive carbon black SP (Super P), graphite, superconducting carbon, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, but is not limited thereto.

[0078] In some specific embodiments, the binder includes any bonding material commonly used in the art, such as at least one of PVDF (polyvinylidene fluoride), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), styrene-butadiene rubber (SBR), water-based acrylic resin and carboxymethyl cellulose (CMC), but is not limited thereto.

[0079] In some specific embodiments, the mass ratio of the negative electrode material, the conductive agent and the binder is 50-99 (e.g., 55, 60, 65, 70, 75, 80, 85, 90 or 95): 0-25 (e.g., 5, 10, 15 or 20): 0.1-25 (e.g., 5, 10, 15 or 20).

[0080] In some specific embodiments, the dry sample includes the following components in percentage by mass: 50% to 99% of negative electrode material, 0% to 25% of conductive agent, and 0.1% to 25% of binder.

[0081] In some specific embodiments, the electrolyte solvent includes any solvent commonly used in the art, such as at least one of an ether solvent and an ester solvent, but is not limited thereto.

[0082] The ether solvent includes, for example, dimethyl ether (DME), dioxolane (DOL), etc., but is not limited thereto.

[0083] The ester solvents include, for example, propylene carbonate (PC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and diethyl carbonate (DEC), but are not limited thereto.

[0084] In some specific embodiments, the nuclear magnetic resonance test includes a low-field nuclear magnetic resonance test. Among them, the low-field nuclear magnetic resonance test has the advantages of fast test speed, short test time, high sensitivity, and non-destructiveness. The principle of this technology is to analyze the physical state of the material by testing the resonance frequency of hydrogen nuclei in the sample in a low-intensity magnetic field.

[0085] In some specific embodiments, the magnetic field strength of the nuclear magnetic resonance test is ≤1.0T, including but not limited to any point value of 1T, 0.9T, 0.8T, 0.6T, 0.5T or a range value between any two of them.

[0086] In some specific embodiments, the echo time of the nuclear magnetic resonance test does not exceed 5ms; including but not limited to any point value of 5ms, 4ms, 3ms, 2ms, 1ms, 0.5ms, 0.1ms or any range value between two of them. The echo time of the nuclear magnetic resonance test has a great influence on the accuracy of the test result. Among them, the echo time refers to the interval time from the excitation of the radio frequency pulse to the collection of the echo signal. In the test, a shorter echo time can reduce the attenuation of the signal. When it exceeds 5ms, the signal of the electrolyte in the small hole in the negative electrode sample cannot be collected, which will make the measured signal low.

[0087] In some specific embodiments, the number of echoes in the nuclear magnetic resonance test is not less than 10,000; including but not limited to any point value of 10,000, 12,000, 13,000, 18,000 or a range value between any two. The number of echoes in the nuclear magnetic resonance test has a great influence on the accuracy of the test result. Among them, the number of echoes is the number of echoes obtained by signal sampling, and is also the number of 180-degree pulses. If the number of echoes is less than 10,000, the validity information in the sample will be lost during the test.

[0088] In some specific embodiments, the waiting time of the nuclear magnetic resonance test does not exceed 10000ms; including but not limited to any point value of 9000ms, 8000ms, 7000ms, 6000ms or any range value between the two. The waiting time of the nuclear magnetic resonance test has a great influence on the accuracy of the test results. Among them, the waiting time is greater than the time required for the longitudinal magnetization vector to basically return to the equilibrium state. Too long a waiting time will extend the time required for the test, and too short a waiting time will cause the signal intensity to weaken. Among them, the minimum waiting time is preferably 3 to 5 times the longitudinal relaxation time (T1), so that the longitudinal magnetization vector can be basically restored. It is understandable that different samples have different longitudinal relaxation times (T1), and T1 is measured by an inversion recovery sequence.

[0089] In some specific embodiments, the cumulative sampling number of the nuclear magnetic resonance test is not less than 4 times, for example, 5 times, 6 times, 7 times, 8 times, 9 times or 10 times. The cumulative sampling number of the nuclear magnetic resonance test has a great influence on the accuracy of the test result. Among them, when the sample signal is weak or the noise is strong, the cumulative sampling number needs to be increased. However, if the cumulative sampling number is too long, the test time will be extended, and if the cumulative sampling number is less than 4 times, the test signal strength will be weak.

[0090] In some specific embodiments, the infiltration is performed under vacuum conditions, and the vacuum degree of the infiltration is 0.1-0.5 MPa, including but not limited to any point value of 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or a range value between any two of them.

[0091] In some specific embodiments, the infiltration time is ≥ 2 h, including but not limited to any point value of 2 h, 4 h, 5 h, 6 h, 8 h, 10 h, 12 h, or a range value between any two of them.

[0092] Infiltration under the above conditions is conducive to complete infiltration, so that the sample is saturated with the electrolyte solvent.

[0093] In some specific implementations, the electrolyte solvent is allowed to completely infiltrate the dry sample, wherein the criterion for complete infiltration is that there are no more bubbles on the surface of the dry sample.

[0094] In some specific implementations, the drying temperature is 110-130° C., and the drying time is 12-24 hours.

[0095] In some specific embodiments, after the drying or the infiltration, the dry weight of the sample is weighed, and the volume of the sample is measured.

[0096] In some specific embodiments, the method for removing the electrolyte solvent on the surface of the sample after infiltration includes: wiping off the electrolyte solvent remaining on the surface of the sample after infiltration.

[0097] In some specific implementations, the dried sample and the negative electrode sample are placed in glass sample bottles (glass test tubes) respectively, and then placed in a nuclear magnetic resonance instrument (low-field nuclear magnetic resonance instrument) to perform a nuclear magnetic resonance test.

[0098] In some specific embodiments, the method of soaking the dry sample in an electrolyte solvent comprises: placing the dry sample in a container filled with an electrolyte solvent, placing the container in a vacuum device, and vacuuming until the pores of the sample are completely soaked (filled) with the electrolyte solvent.

[0099] In a second aspect, the present invention provides application of the negative electrode material true density testing method in the preparation of secondary batteries.

[0100] The secondary batteries include but are not limited to lithium-ion batteries and sodium-ion batteries.

[0101] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0102] Example 1

[0103] The negative electrode material true density testing method provided in this embodiment includes the following steps:

[0104] (1) Using a low-field nuclear magnetic resonance instrument, the nuclear magnetic resonance signal of the electrolyte solvent of different masses was measured, wherein the electrolyte solvent was propylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1, and the density of the electrolyte solvent was 1.03 g / cm 3 The linear regression method was used to fit the linear equation (i.e., linear equation), with the NMR signal as the dependent variable and the mass of the electrolyte solvent as the independent variable, as y=3381×x, where x is the mass of the electrolyte solvent, y is the NMR signal, and 3381 is the slope. The linear equation can be found in Figure 1 shown.

[0105] (2) The negative electrode materials to be tested, hard carbon HNA104 and conductive carbon black SP (with a true density of 2.05 g / cm 3 ) and binder PVDF (true density 1.77g / cm 3 ) are mixed evenly and pressed into a cylinder with a diameter of 6.12 mm using a tabletting mold, and then dried in an oven at 120°C for 12 hours, and the sample is taken out to obtain a dry sample, and its dry weight is weighed and its height is measured with a vernier caliper. That is, the content of each component in the dry sample is calculated by mass percentage: 95.6% of negative electrode material, 1.4% of conductive agent and 3% of binder.

[0106] The dried sample is placed in a container containing an electrolyte solvent, the composition of the electrolyte solvent is the same as that in step (1), and the container is placed in a vacuum device, and vacuumed at a pressure of 0.1 MPa until the sample pores are completely soaked in the electrolyte solvent (the soaking time is 4 hours), soaked in the electrolyte solvent, and after the completely soaked sample is taken out, the electrolyte solvent remaining on the surface of the sample after soaking is wiped off to obtain a negative electrode sample. That is, the shape of the negative electrode sample is a cylinder with a diameter of 6.12 mm.

[0107] (3) The dried sample and negative electrode sample prepared above are placed in glass sample bottles respectively, and the glass sample bottles are placed in a low-field nuclear magnetic resonance instrument for low-field nuclear magnetic resonance testing. The magnetic field intensity of the nuclear magnetic resonance test is 1.0T, the echo time is 0.5ms, the number of echoes is 10000, the waiting time is 10000ms, and the cumulative sampling times is 4 times. The nuclear magnetic resonance signal of the dried sample is measured to be A0, and the nuclear magnetic resonance signal of the negative electrode sample is measured to be A1. A=A1-A0 is calculated, where A is the nuclear magnetic resonance signal corresponding to the pore volume in the negative electrode sample.

[0108] Then the true density of the negative electrode material is calculated by the following calculation method:

[0109] Substituting A into the linear equation y=3381×x, the mass m0 of the electrolyte solvent in the negative electrode sample is obtained (ie, y=A, and the calculated x is m0).

[0110] V0=m 0 / ρ0; where V0 is the volume of the electrolyte solvent, in cm 3 ; m0 is the mass of the electrolyte solvent in the negative electrode sample, in g; ρ0 is the density of the electrolyte solvent, in g / cm 3 .

[0111] in, is the porosity of the negative electrode sample; V1 is the volume of the negative electrode sample, in cm 3 , V1=π×(d / 2) 2 ×h, where d is the diameter of the negative electrode sample in cm, and h is the height of the negative electrode sample in cm.

[0112] V2=V1-V0; V2 is the total solid volume of the negative electrode sample, in cm 3 .

[0113] V3=m1×P1 / ρ P ; Where V3 is the volume of the binder, in cm 3 ; m1 is the mass of the negative electrode sample, in g; P1 is the mass fraction of the binder in the dry sample; ρ P is the true density of the binder, in g / cm 3 .

[0114] V4=m1×P2 / ρ S ; Where V4 is the volume of the conductive agent, in cm 3 ; P2 is the mass fraction of the conductive agent in the dry sample; ρ S is the true density of the conductive agent, in g / cm 3 .

[0115] V5 = V2-V3-V4; V5 is the true volume of the negative electrode material, in cm 3 .

[0116] True density of negative electrode material ρ H =m1×P H / V5; where P H is the mass fraction of the negative electrode material in the dry sample; ρ H The unit is g / cm 3 .

[0117] According to the above method, the true density ρ of the three groups of negative electrode materials hard carbon HNA104 was calculated respectively. H , the average value is 1.460g / cm 3 The true density of the above three groups of negative electrode materials is H The parameters and results of the calculation process are shown in Table 1.

[0118] Table 1 True density ρ of negative electrode materials H Parameters and results of the calculation process

[0119]

[0120] The theoretical liquid injection volume ratio obtained by taking it into account in the battery cell design is 88.07%, and the capacity retention rate of the battery cell after 500 cycles of 4.0V and 1C is 95.72%.

[0121] Example 2

[0122] The method for testing the true density of the negative electrode material provided in this embodiment is basically the same as that in embodiment 1, except that the negative electrode material is hard carbon HNA102, and the fitting equation of the marking line obtained in this embodiment 2 is y=5551.6×x. Figure 2 The true density ρ of five groups of negative electrode materials hard carbon HNA102 was calculated respectively. H , the average value is 1.449g / cm 3 Among them, the true density of the negative electrode material hard carbon HNA102 is H The parameters and results of the calculation process are shown in Table 2.

[0123] Table 2 True density ρ of negative electrode materials H Parameters and results of the calculation process

[0124]

[0125] The theoretical liquid injection volume ratio obtained by taking it into account in the battery cell design is 88.81%, and the capacity retention rate of the battery cell after 500 cycles of 4.0V and 1C is 96.62%.

[0126] Comparative Example 1

[0127] The true density of the three groups of negative electrode materials of Example 1 was tested by BET method, and the average value was taken. The true density was 2.309 g / cm 3 Under the same cell design as in Example 1, the theoretical liquid injection volume accounts for 70.16%, and the capacity retention rate of the cell after 500 cycles at 4.0V and 1C is 82.41%.

[0128] By comparing Example 1 and Comparative Example 1, it can be seen that the cycle performance of Example 1 is better, so the test method of the true density of the negative electrode material of Example 1 is more accurate.

[0129] Comparative Example 2

[0130] The true density of five groups of negative electrode materials of Example 2 was tested by BET method, and the average value was taken. The true density was 2.135 g / cm 3 Under the same cell design as in Example 2, the theoretical liquid injection volume accounts for 71.76%, and the capacity retention rate of the cell after 500 cycles at 4.0V and 1C is 84.72%.

[0131] By comparing Example 2 and Comparative Example 2, it can be seen that the cycle performance of Example 2 is better, so the test method of the true density of the negative electrode material of Example 2 is more accurate.

[0132] In summary, the negative electrode material true density testing method provided by the present invention tests the porosity of the negative electrode material when it is immersed in an electrolyte solvent, and excludes tiny pores that the electrolyte solvent molecules cannot enter. The obtained true density is more suitable for the design of the battery cell injection amount, and has the advantages of high accuracy, fast testing speed, high sensitivity, simple operation and non-destructiveness.

[0133] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for testing the true density of negative electrode materials, characterized in that: The steps include: The negative electrode material to be tested is mixed with a binder or the negative electrode material to be tested, a conductive agent and a binder are mixed, and then pressed and dried to obtain a dry sample; The dried sample is immersed in an electrolyte solvent, and the electrolyte solvent on the surface of the immersed sample is removed to obtain a negative electrode sample; The dry sample and the negative electrode sample are respectively subjected to nuclear magnetic resonance testing, and then the true density of the negative electrode material is obtained by calculation.

2. The method for testing the true density of negative electrode materials according to claim 1, characterized in that: Before the calculation, the nuclear magnetic resonance signal amount of the electrolyte solvent at different masses is measured, and the linear equation is obtained by taking the nuclear magnetic resonance signal amount as the dependent variable and the mass of the electrolyte solvent as the independent variable.

3. The method for testing the true density of negative electrode materials according to claim 2, characterized in that: The nuclear magnetic resonance signal of the dry sample is measured to be A0, and the nuclear magnetic resonance signal of the negative electrode sample is measured to be A1, A=A1-A0, wherein A is the nuclear magnetic resonance signal corresponding to the pore volume of the negative electrode sample.

4. The method for testing the true density of negative electrode materials according to claim 3, characterized in that: The calculation method comprises: substituting A into the linear equation to obtain the mass m0 of the electrolyte solvent in the negative electrode sample, and then calculating the true density ρ of the negative electrode material. H .

5. The method for testing the true density of negative electrode materials according to claim 4, characterized in that: The true density of the negative electrode material ρ H The specific calculation methods include: V0=m 0 / ρ0; wherein, m0 is the mass of the electrolyte solvent in the negative electrode sample, in g; ρ0 is the density of the electrolyte solvent, in g / cm 3 ; φ=(V0 / V1)×100%;wherein, φ is the porosity of the negative electrode sample; V0 is the volume of the electrolyte solvent, in cm 3 ; V1 is the volume of the negative electrode sample, in cm 3 ; V2 = V1 - V0; wherein V2 is the total solid volume of the negative electrode sample, in cm 3 ; V3=m1×P1 / ρ P ; Wherein, V3 is the volume of the binder, in cm 3 ; m1 is the mass of the negative electrode sample, in g; P1 is the mass fraction of the binder in the dry sample; ρ P is the true density of the binder, in g / cm 3 ; V4=m1×P2 / ρ S ; Wherein, V4 is the volume of the conductive agent, in cm 3 ; P2 is the mass fraction of the conductive agent in the dry sample; ρ S is the true density of the conductive agent, in g / cm 3 ; V5 = V2 - V3 - V4; wherein V5 is the true volume of the negative electrode material, in cm 3 ; ρ H =m1×P H / V5; where P H is the mass fraction of the negative electrode material in the dry sample; ρ H The unit is g / cm 3 .

6. The method for testing the true density of negative electrode materials according to claim 4, characterized in that: At least one of the following conditions is met: (1) The shape of the negative electrode sample is a cylinder, and V1 = π × (d / 2) 2 ×h; wherein, d is the diameter of the negative electrode sample, in cm; h is the height of the negative electrode sample, in cm; (2) The shape of the negative electrode sample is a rectangular parallelepiped, and V1=a×b×h; wherein a is the length of the negative electrode sample, in cm; b is the width of the negative electrode sample, in cm; and h is the height of the negative electrode sample, in cm; (3) The shape of the negative electrode sample is a sphere, and V1 = (4 / 3) × π × r 3 ; Wherein, r is the radius of the negative electrode sample, in cm; (4) The shape of the negative electrode sample is a prism, and V1=S×h; wherein S is the bottom area of ​​the negative electrode sample, in cm 2 ; h is the height of the negative electrode sample, in cm.

7. The method for testing the true density of negative electrode materials according to any one of claims 1 to 6, characterized in that: At least one of the following conditions is met: (1) The negative electrode material comprises at least one of a carbon material, a silicon material and a silicon-carbon composite material; (2) The conductive agent includes at least one of conductive carbon black SP, graphite, superconducting carbon, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; (3) The binder comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, styrene-butadiene rubber, water-based acrylic resin and carboxymethyl cellulose; (4) The mass ratio of the negative electrode material, the conductive agent and the binder is 50-99:0-25:0.1-25; (5) The electrolyte solvent includes at least one of an ether solvent and an ester solvent.

8. The method for testing the true density of negative electrode materials according to any one of claims 1 to 6, characterized in that: At least one of the following conditions is met: (1) The nuclear magnetic resonance test includes a low-field nuclear magnetic resonance test; (2) The magnetic field strength of the nuclear magnetic resonance test is ≤1.0T; (3) The echo time of the nuclear magnetic resonance test does not exceed 5 ms; (4) The number of echoes in the nuclear magnetic resonance test is not less than 10,000; (5) The waiting time of the NMR test does not exceed 10000ms; (6) The cumulative sampling times of the NMR test is no less than 4 times.

9. The method for testing the true density of negative electrode materials according to any one of claims 1 to 6, characterized in that: At least one of the following conditions is met: (1) The infiltration is performed under vacuum conditions, and the vacuum degree of the infiltration is 0.1 to 0.5 MPa; (2) The infiltration time is ≥ 2h.

10. Use of the method for testing the true density of negative electrode materials according to any one of claims 1 to 9 in preparing secondary batteries.

Citation Information

Patent Citations

  • Method of testing porosity of pole piece

    CN103134744A

  • Method for accurately measuring nuclear magnetic resonance porosity of oil-containing shale

    CN105866002A

  • Method for measuring effective porosity of lignite based on low field nuclear magnetic resonance technology

    CN107271347A

  • Method for testing porosity of lithium ion battery pole piece

    CN111398127A

  • Porosity determination method of lithium ion battery pole piece

    CN112362549A